Z-12=6
you take the 12 and add it to both sides making it look like:
z-12+12=6+12
which also looks like
z-0=6+12
z-0 = z
so now you have
z=6+12
6+12 = 18
SO Z=18!!!
your answer is 18
Answer:
±35
Step-by-step explanation:
sqrt(49*25)=sqrt(49)*sqrt(25)=±7*±5=±35
Answer:
Step-by-step explanation:
(12 - 2)/(2 - 7) = 10/-5 = -2
y - 12 = -2(x - 2)
y - 12 = -2x + 2
y = -2x + 14
Answer:
<em>1. </em><em>B. $20</em>
<em>2.</em><em>C. 19%</em>
<em>3. </em>D. not here
Step-by-step explanation:
1. info we know
25+45+10+25+15+10 = 130
we need 20 more dollars
2. 25/130 x/100
cross multiply
2500/ 130x
divide
19 = x
3. same steps as last time
35/130 x/100
3500/130x
29%
Responder:
<em>a) 1
</em>
<em>b) 12
</em>
<em>c) 3
</em>
<em>d) -1 y 3
</em>
Explicación paso a paso:
Dadas las siguientes ecuaciones;
a) x²-x =0
x² = 0+x
x² = x
x = 1
b) -x²+12x = 0
-x² = -12x
x² = 12x
x = 12
c) 3x² - 9x = 0
Suma 9x a ambos lados
3x²-9x+9x = 0+9x
3x² = 9x
3x = 9
x = 9/3
x = 3
d) x²-2x-3 = 0
x²-3x+x-3 = 0
x(x-3)+1(x-3) = 0
(x+1)(x-3) = 0
x+1 = 0 y x-3 = 0
x = -1 y 3